Peningkatan Kemampuan Menulis Aksara Jawa dengan Metode Ulum Tuan Baik Menggunakan Media Lusapa - Tri Muryanti (Direktorat GTK Pendidikan Dasar Kemendikbud R.I., 2018)
The research objective was to improve the students’ writing skill in Javanese through Ulum Tuan Baik method with Lusapa media for the seventh-grade students at the State Junior Secondary School geri 2 Tarokan in the academic year of 2017/2018. This research was designed using a classroom research. Data were collected by administering a test to obtain quantitative data. Whereas, a non-test was administered to aquire qualitative data as well. Data were analyzed quantitatively and qualitatively. The research results show that the students’ writing skill in Javanese using Ulum Tuan Baik method with Lusapa media was improved. The students’ improvements are improved from 67.96 in cycle 1 and 82.96 in cycle 2.